Bilateral optic neuritis as a first presentation of lymph node tuberculosis. Issue 1 (28th July 2021) - Keshavan, Ashvini; McAnena, Lisa; Acheson, James F; Booth, Helen; Plant, Gordon T; Khaleeli, Zhaleh
Abstract : Tuberculosis (TB) may affect the nervous system in many ways. We describe an immunocompetent teenage girl with lymph node TB who had first presented with bilateral optic neuritis. Detailed history identified features inconsistent with immune-mediated optic neuritis. Several unusual features prompted further investigation, including transient visual obscurations without raised intracranial pressure, prominent disc swelling and absence of laboratory findings to support an immune-mediated cause. Whole body PET/MR imaging identified widespread mediastinal and supraclavicular lymphadenopathy. Despite no known TB contacts, a negative interferon gamma release assay and a normal chest X-ray, a targeted lymph node biopsy confirmed TB.